2014
DOI: 10.5194/angeo-32-1427-2014
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic E layer at mid-latitudes: average properties and influence of atmospheric tides

Abstract: Abstract. This paper describes a study of the daily variability shown by the main characteristics of the sporadic E (Es) layer, that is the top frequency (ftEs) and the lowest virtual height (h'Es). The study is based on ionograms recorded by the Advanced Ionospheric Sounder by the Istituto Nazionale di Geofisica e Vulcanologia (AIS-INGV) ionosondes installed in the ionospheric stations at Rome (41.8 • N, 12.5 • E) and Gibilmanna (37.9 • N, 14.0 • E), Italy, during the summer (June, July, August and September)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
38
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 22 publications
5
38
1
2
Order By: Relevance
“…The data set considered in this study is constituted by hourly values of foEs and fbEs recorded at the ionospheric station of Rome (41.8°N, 12.5°E), Italy, from January 1976 to December 2009, and validated according to the URSI (International Union of Radio Science) standard (Piggott & Rawer 1972). Data were downloaded from the electronic Space Weather upper atmosphere (eSWua) database (http://www.…”
Section: Data Set Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data set considered in this study is constituted by hourly values of foEs and fbEs recorded at the ionospheric station of Rome (41.8°N, 12.5°E), Italy, from January 1976 to December 2009, and validated according to the URSI (International Union of Radio Science) standard (Piggott & Rawer 1972). Data were downloaded from the electronic Space Weather upper atmosphere (eSWua) database (http://www.…”
Section: Data Set Analysis and Resultsmentioning
confidence: 99%
“…We focused our attention on the mean around 12:00 LT, because it is known that mid-latitude Es layers present a maximum of electron density right around this local time hour (i.e. Bossolasco & Elena 1963;Pignalberi et al 2014). Table 2 shows the occurrence percentage of the various types of Es traces, l(ow), c(usp) and h(igh), recorded between 10:00 LT and 14:00 LT, for the whole data set from January 1976 to December 2009.…”
Section: Data Set Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, from a single ionogram it would not be possible to derive the dynamics of the ionospheric layers. On the contrary, the HTI analysis proposed by Haldoupis et al (2006), and recently used by Pignalberi et al (2014) and Oikonomou et al (2014), to investigate how tidal waves influence the Es dynamics, considers a specific frequency range and, by using a series of ionograms, allows the study of the aforementioned dynamics. The output of the HTI analysis is a plot of the intensity of the energy received by the ionosonde, after being reflected by the ionosphere, versus the 24 h of the day, for a definite frequency range, and for the same height range of the ionogram.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Observations revealed that the diurnal and semidiurnal tides are the main agents that control the formation and altitude descent of sporadic E layers. Pignalberi et al also used height-time-intensity (HTI) which describe the daily variability of the sporadic E (Es) layer, the top frequency (ftEs) and the lowest virtual height (h'Es) [18,19]. The height-time-Intensity (HTI) study, along with a fast Fourier transform analysis, showed that a semidiurnal periodicity characterizes the Es layer most accurately in June and July, while in August and September the daytime semidiurnal periodicity becomes weaker and the role of the diurnal periodicity is consequently highlighted.…”
Section: Introductionmentioning
confidence: 99%